2015
DOI: 10.1186/s12906-016-1023-2
|View full text |Cite
|
Sign up to set email alerts
|

Protective activity of kudzu (Pueraria thunbergiana) vine on chemically-induced hepatotoxicity: in vitro and in vivo studies

Abstract: BackgroundKudzu (Pueraria thunbergiana) root has long been used in Traditional Chinese Medicine. However, the vine of the kudzu plant has been considered waste material. This study aimed to investigate the hepatoprotective properties of the kudzu vine.MethodsWe created 0 %, 30 %, 70 %, and 95 % ethanolic kudzu vine extracts. The isoflavone contents of kudzu vine extract were quantified by high-performance liquid chromatography. Tertiary-butylhydroperoxide (t-BHP) was added to human liver-derived HepG2 cells, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…The proprietary liquid DA-5513 formulation was developed using seven herbal extracts, including GMT-ALC-5L (fermented rice embryo and bean extract), Curcuma longa L. , Trapa japonica Flerov., Silybum marianum L. , Paullinia cupana Mart., Pueraria thunbergiana Benth., and honey. These natural products have been used in traditional oriental medicines to prevent alcohol-induced hangover and protect the liver against diverse hepatotoxins such as ethanol, carbon tetrachloride, antitubercular agents, and thioacetamide [ 14 15 16 17 18 19 20 ].…”
mentioning
confidence: 99%
“…The proprietary liquid DA-5513 formulation was developed using seven herbal extracts, including GMT-ALC-5L (fermented rice embryo and bean extract), Curcuma longa L. , Trapa japonica Flerov., Silybum marianum L. , Paullinia cupana Mart., Pueraria thunbergiana Benth., and honey. These natural products have been used in traditional oriental medicines to prevent alcohol-induced hangover and protect the liver against diverse hepatotoxins such as ethanol, carbon tetrachloride, antitubercular agents, and thioacetamide [ 14 15 16 17 18 19 20 ].…”
mentioning
confidence: 99%
“…Several studies have suggested that the antioxidant activity against free radicals may be an important mechanism of hepatoprotection [ 20 ]. Many natural products containing flavonoids, coumarins, and polyols have been investigated for the development as antioxidants [ 4 , 15 , 21 , 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…CCl 4 is used to induce liver toxicity to allow the testing of drugs for their hepatoprotective activities. Silymarin is used as standard hepatoprotective compound since it is reported to have a protective effect on the hepatocytes [ 4 , 14 ]. In the present study, we also used CCl 4 to induce hepatotoxicity in rats.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations